(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The upholstery with inner spring units, is composed of materials, which have various stress-strain behavior under load. In the work is studied softness and behavior of structures composed of different combinations of upholstery materials. The type of the innerspring unit, materials and thickness of the upper layers are changed. As criteria for evaluation of the specimens are used coefficients of softness and requirements for general deformation of the structure of the upholstery for seat and back elements. Conclusions are made and recommendations for their application in the structure of upholstered furniture.